Redefining: Cultural Impression in Princely States During Colonial Period - Sasi, Ashwini (Resourceedings, 2018)
India is well diverse with a variety of cultural and traditional practices. Impact of age-old practices redefined the idea of culture and tradition, not only as a hereditary system, but also as part of art and architecture. Factors such as the cultural changes between North and South India, impact of the British, changes in spatial organization and patriarchy and matrilineal system drew an impact on cultural impression of India through time.Palaces (04th —18th century) and the lifestyle of the heirs, being a soul example to exhibit the Indian uniqueness, gradually inclined towards British culture and morals. This influence brought a change in the architectural design of palaces, which is the core study area in the thesis.Comparing the architectural planning of palaces from the 13th to the 18th century showed a clear change on how British influenced Indian palace design. This became one of the finest reasons to identify cities with palaces based on their culture and tradition, and on art and architecture. In addition to finding how it has brought the influential change and what is the present scenario of the same palaces.The architectures that were adopted in India was a form of true traditional architecture which is been followed through a very long time and hence it was collaborated with Italian, French, Indo Sarcenic or European style.